Stakeholder Perceptions of Offshore Wind Power: A Fuzzy Cognitive Mapping Approach. Issue 8 (2nd August 2016) - Kermagoret, Charlène; Levrel, Harold; Carlier, Antoine; Ponsero, Alain
ABSTRACT: Using the method of fuzzy cognitive mapping, this study explores stakeholder attitudes toward offshore wind energy. The survey was conducted with local communities of the Bay of Saint-Brieuc, where an offshore wind farm is under development. It was used to record the stakeholder perceptions of social, ecological, and economic impacts and the expression of expected compensation for negative impacts. Distribution and interaction among the data were analyzed through multiple correspondence analysis. Our study illustrates a gap between positive impacts associated with sustainable development perceived at the national level and more negative impacts perceived by local communities. The expression of expected compensation is dependent on the perceived impacts. This study highlights the place attachment of local stakeholders and thus suggests developing offshore wind farms with respect to territorial integrity and its heritage dimension in order to improve social acceptability.